2003
DOI: 10.1002/ijc.11669
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms result in impaired membrane localization and reduced atpase activity in multidrug transporter ABCG2

Abstract: ABCG2/MXR/ABCP1/BCRP is a member of the ATP-binding cassette membrane transporter, which consists of six transmembrane regions and one ATP-binding cassette. The transporter is known to be involved in the efflux of various anticancer compounds such as mitoxantrone, doxorubicin and topoisomerase I inhibitor. In this study, we analyzed the effects of polymorphisms in ABCG2, V12M and Q141K on transporter function. When polarized LLC-PK1 cells were transfected with variant ABCG2, drug-resistance to topoisomerase I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
208
5
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(230 citation statements)
references
References 30 publications
12
208
5
5
Order By: Relevance
“…9,[12][13][14][15] The results are also concordant with the findings of Wang et al 11 who suggested that among linked ABCB1 SNPs, the 3435T4C silent variation is responsible for the differences in gene expression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…9,[12][13][14][15] The results are also concordant with the findings of Wang et al 11 who suggested that among linked ABCB1 SNPs, the 3435T4C silent variation is responsible for the differences in gene expression.…”
Section: Discussionsupporting
confidence: 86%
“…The twelfth amino acid is placed within the first transmembrane domain and the 12M allele may disturb the protein's proper membrane localization resulting in decreased cellular transport. 12,13 Data on the functional relevance of these SNPs and the controversies have been reviewed recently by many authors. 14,15 In order to assess the possible value of these SNPs in the prediction of neurotoxic side effects of chemotherapy, we have studied a large cohort of patients treated for childhood acute lymphoblastic leukaemia (ALL).…”
Section: Introductionmentioning
confidence: 99%
“…42 Also, impaired membrane localization caused by single-nucleotide polymorphisms results in a decline of ABCG2 ATPase activity. 43 Whether this applies to ABCG2 function in the in vivo situation must be established.…”
Section: Abcg2 In the Biliary Tract S Aust Et Almentioning
confidence: 99%
“…In vitro and in vivo studies, on the other hand, have shown this SNP to be disruptive of BCRP activity. Clinical trials with diflomotecan, a novel anticancer agent inhibiting topoisomerase I, showed decreased plasma concentration in patients heterozygous for this SNP compared to wild type [33,34]. Recently, the increased placental crossing of the antidiabetic agent glyburide (glibenclamide) has been demonstrated in stably transfected human embryonic kidney (HEK)-293 cells expressing the polymorphic ABCG2 (Q141K) [35].…”
Section: Breast Cancer Resistance Protein (Bcrp)mentioning
confidence: 99%